Morphometry of Asian House Shrew (Suncus murinus) in Jahangirnagar University Campus (Bangladesh Journal of Zoology, 2016)
A study was conducted on morphometry of Asian House Shrew, Suncus murinus at Jahangirnagar University campus, Savar, Dhaka from December, 2010 to November, 2011. A total of 85 shrews (55 males and 30 females) were studied for morphometric analysis. The body length of shrews varied from 13cm to 18 cm (mean 15.36, sd±1.17). Males were significantly differed from females in size which made them sexually dimorphic (t = 10.02, df = 83, p< 0.005). The body length of males ranged from 14.5 cm to 18 cm (mean = 16, sd±0.82) and in females it ranged from 13 cm to 15.5 cm (mean = 14.19, sd±0.74). The body weight of shrews varied from 45 gm to 138 gm (mean = 85.52, sd±25.6). The weight of males ranged from 65 gm to 138 gm (mean = 99.6, sd±20.03) whereas the body weight of females ranged from 45 gm to 82 gm (mean = 59.73, sd±10.54). Body length was positively correlated to the body weight (r = 0.917) as well as tail length (r = 0.673) and limbs length (forelimb length, r = 0.875 and hindlimb length, r = 0.971) and found to be significant at 1% level of significance.Bangladesh J. Zool. 43(2): 313-319, 2015